Comprehensive genomic profiling of colorectal cancer patients reveals differences in mutational landscapes among clinical and pathological subgroups - Li, Peng; Meng, Qingyu; Xue, Yonggan; Teng, Zhipeng; Chen, Hanlin; Zhang, Junli; Xu, Yang; Wang, Sha; Yu, Ruoying; Ou, Qiuxiang; Wu, Xue; Jia, Baoqing (Frontiers in Oncology, 2022)
With the widespread of colonoscopy, colorectal cancer remains to be one of the most detrimental types of cancer. Though there were multiple studies investigating the genomic landscape of colorectal cancer, a comprehensive analysis uncovering the differences between various types of colorectal cancer is still lacking. In our study, we performed genomic analysis on 133 patients with colorectal cancer. FAT1, PKHD1 mutations, and altered Hippo pathway genes were found to be enriched in early-onset colorectal cancer. APOBEC signature was prevalent in microsatellite stable (MSS) patients and was related to lymph node metastasis. ZNF217 mutations were significantly associated with early-stage colorectal cancer. In all, this study represents a comprehensive genomic analysis uncovering potential molecular mechanisms underneath different subgroups of colorectal cancer thus providing new targets for precision treatment development.